2003
DOI: 10.1046/j.1365-294x.2003.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the endangered wild apple (Malus sylvestris (L.) Mill.) in Belgium as revealed by amplified fragment length polymorphism and microsatellite markers

Abstract: The genetic variation within and between wild apple samples (Malus sylvestris) and cultivated apple trees was investigated with amplified fragment length polymorphisms (AFLP) and microsatellite markers to develop a conservation genetics programme for the endangered wild apple in Belgium. In total, 76 putative wild apples (originating from Belgium and Germany), six presumed hybrids and 39 cultivars were typed at 12 simple sequence repeats (SSR) and 139 amplified fragment length polymorphism (AFLP) loci. Princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
82
2
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 43 publications
19
82
2
4
Order By: Relevance
“…However, this is in line with the findings of Coart et al (2003) studying hybridization between the two species in Belgium and Germany. In this study they found 3 hybrids out of a total of 76 putative wild individuals studied.…”
Section: Hybridization Between Malus Sylvestris and Malus ×Domesticasupporting
confidence: 89%
See 4 more Smart Citations
“…However, this is in line with the findings of Coart et al (2003) studying hybridization between the two species in Belgium and Germany. In this study they found 3 hybrids out of a total of 76 putative wild individuals studied.…”
Section: Hybridization Between Malus Sylvestris and Malus ×Domesticasupporting
confidence: 89%
“…Potentially, homoplasy can pose a problem in delineating the relationship between taxonomic units (Goldstein & Pollock, 1997). Nevertheless, concordance between results obtained using AFLP and microsatellite markers in the aforementioned study of Coart et al (2003) suggests that this is not an issue for the present study.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations